Reconnecting Creativity: Designing Learning Kits through Hands-On Material Exploration for Early Childhood Development - Amelia, Amanda; Paskevicius, Algirdas; Ono, Kenta (Jurnal Desain Indonesia., 2025)
Designing creative learning kits for children during early childhood development requires a deep understanding of how they interact with simple, open-ended materials. This study explored the idea that designers must reconnect with hands-on material experiences to create meaningful and effective kits. Using the "Materials & Creativity" class at Chiba University as a case study, design students followed Kolb’s Experiential Learning Cycle, engaging in self-expression, brainstorming, prototyping, and peer testing. The findings highlight that direct interaction with materials plays a crucial role in reawakening creativity and aligning design processes with children’s natural play behaviors. Peer feedback helped refine the learning kits, ensuring their usability and educational value. This study suggests integrating material exploration and experiential learning principles into design education fosters creative thinking and effective solutions.